Composite Yttrium‐Carbonaceous Spheres Templated Multi‐Shell YVO4 Hollow Spheres with Superior Upconversion Photoluminescence. Issue 9 (23rd December 2016) - Zong, Lingbo; Xu, Jie; Jiang, Shuaiyu; Zhao, Kun; Wang, Zumin; Liu, Porun; Zhao, Huijun; Chen, Jun; Xing, Xianran; Yu, Ranbo
Abstract : Complex oxide YVO4 multi‐shell hollow spheres with uniform morphologies and controllable shell numbers are successfully prepared by using a newly developed and general composite yttrium‐carbonaceous sphere templated approach. The prominent upconversion luminous intensity of the YVO4 :Yb 3+ /Er 3+ hollow spheres might be attributed to the enhanced near‐infrared excitation light harvesting efficiency originated from the multiple reflections.